Expedition To Armenian Forests: Any Unique TreeSpecies Growing There? Towards Treebanking of Modern Eastern Armenian - Vardanyan, L. (Институт языкознания РАН)
This paper is aimed at sketching out an outline about the research work in progress in frames of PhD 2006-2008 program “Linguistica generale, storica, applicata, computazionale e delle lingue moderne”, carried out at the Department of Linguistics "Tristano Bolelli", University of Pisa. We propose and support the practical and theoretical background for developing a sample of a syntactically annotated corpus (otherwise called treebank) for Modern Eastern Armenian. The acknowledged lack and need for descriptive studies on Armenian language resources stands for good reason to set and accomplish such task. Basing on the conviction that only the annotated linguistic data may gain their real value for linguistic observations and research, we will present different annotation levels and formats of corpora. We target the dependency structures description in the form of syntactic functions (manual) annotation of the naturally occurring sentences in a corpus of written Eastern Armenian. The project’s current focus of study is building an annotation scheme alongside setting forth a syntactic tagset to be further applied on a morphologically analyzed corpus on surface syntax level.
Keywords: Linguistics